Particles in the coastal ocean : theory and applications - Lynch, Daniel R. (Cambridge : Cambridge University Press, 2015)
The coastal ocean comprises the semi-enclosed seas on the continental shelf, including estuaries and extending to the shelf break. This region is the focus of many serious concerns, including coastal inundation by tides, storm surges or sea level change; fisheries and aquaculture management; water quality; harmful algal blooms; planning of facilities (such as power stations); port development and maintenance; and oil spills. This book addresses modeling and simulation of the transport, evolution and fate of particles (physical and biological) in the coastal ocean. It is the first to summarize the state of the art in this field and direct it toward diverse applications, for example in measuring and monitoring sediment motion, oil spills and larval ecology. This is an invaluable textbook and reference work for advanced students and researchers in oceanography, geophysical fluid dynamics, marine and civil engineering, computational science and environmental science.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Coastal sediments -- Mathematical models; Oceanography -- Simulation methods; Dynamics of a particle -- Simulation methods; Continental shelf -- Simulation methods